Ekofeminisme pada Tokoh San dalam film “Princess Mononoke” Karya Sutradara Hayao Miyazaki - Alisca Putri Dirgantari (PANTUN, 2020)
This study focuses on the perspective of eco-feminism as a theory of environmental ethics in the film "Princess Mononoke" (1997) by Hayao Miyazaki. This study analyzes how a human girl who was raised by the wolf goddess (Moro) named San who considers herself a wolf. Her main concern is protecting the forest and the animals living with her from the human race that has harassed and destroyed nature for industrial purposes. San shows the efforts and ethics of eco-feminism as well as Deep Ecology in opposing the exploitation of nature and the capitalist system by Lady Eboshi, the leader of Iroha Town who is considered the source of the problem. Environmentalist issues and modernization are in sharp opposition to the detriment of nature as well as humans. The data are taken from the film "Princess Mononoke" by Hayao Miyazaki in the form of dialogues, quotes, phrases and descriptions based on the Environmental Ethics of Ecofeminism specific to the San character. San is a symbol of women who fight against human arrogance which is the main cause of the destruction of nature.Keywords: Feminism, Ecofeminism, Nature, Capitalism.